2006
DOI: 10.1080/08039480600937066
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Depression Scale and the Cornell Scale for Depression in Dementia. A validity study

Abstract: The study is a validation study of two psychogeriatric depression rating scales, The Geriatric Depression Scale (GDS) and the Cornell Scale for Depression in Dementia (CSDD). The sensitivity and specificity, and the convergent and criterion validity of the two scales as well as the inter-rater reliability of the CSDD are reported. Two independent clinicians using the ICD-10 for depression and dementia, the Clinical Global Impression (CGI), the Hamilton Depression rating scale 17-items and the Mini-Mental-State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(190 citation statements)
references
References 13 publications
8
177
0
5
Order By: Relevance
“…The mean score of 8 in the group of patients with minor depression in that study has been used as a cutoff point. Kørner et al [25] reported a very high sensitivity (0.93) and specificity (0.97) with a cutoff point of 6 in a group of outpatients including patients both with and without dementia, and the AUC was 0.98. In this study, spouses of the patients were used as controls, which according to Sackett’s definition, is not a valid contrast group [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean score of 8 in the group of patients with minor depression in that study has been used as a cutoff point. Kørner et al [25] reported a very high sensitivity (0.93) and specificity (0.97) with a cutoff point of 6 in a group of outpatients including patients both with and without dementia, and the AUC was 0.98. In this study, spouses of the patients were used as controls, which according to Sackett’s definition, is not a valid contrast group [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown it to be valid in patients both with and without dementia [25,36], while others have found it incapable of differentiating between depressed and not depressed patients [37]. The cutoff points with the best sensitivity and specificity differ, and probably depend on cultural differences, patient populations and different study designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disability was evaluated with the number of activities of daily living (ADL) preserved using the index proposed by Katz et al 12 , while cognitive status and depressive mood with 30-items minimental state examination (MMSE) 13 and geriatric depression scale (GDS) 14 , respectively.…”
Section: Clinical Datamentioning
confidence: 99%
“…GDS-15 scores range from 0 to 15, with higher scores indicative of greater depression severity. Studies provide support for internal consistency, reliability, and convergent validity with other measures of depression and discriminant validity [25]. Adequate internal consistency was found for the GDS-15 (KR-20 = 0.67) in the present sample of older VA patients.…”
Section: Methodsmentioning
confidence: 68%